Localized pain hypersensitivity in older women with cervicogenic headache: A quantitative sensory testing study - Jenjira Assapun (2018)
© 2017 by Quintessence Publishing Co Inc. Aims: To investigate pain sensitivity by using quantitative sensory testing in older women with and without cervicogenic headache. Methods: A total of 18 older women (mean age ± standard deviation [SD] 64.28 ± 3.21 years) with cervicogenic headache and 17 healthy controls (65.18 ± 3.89 years) participated in the study. Pain thresholds (pressure, heat, and cold) and suprathreshold heat pain ratings (at 45°C, 47°C, and 49°C) were measured over the temporalis muscle, upper cervical spine, and tibialis anterior muscle. Analysis of variance was used to determine differences in pain outcomes between groups. Results: Compared to the control group, cold pain threshold in the cervicogenic headache patients was significantly decreased in the upper cervical region (P =.04) but not over the temporalis and tibialis anterior muscles (P > .05). There were no significant between-group differences in pressure pain threshold, heat pain threshold, or suprathreshold heat pain ratings at any sites (P > .05). Conclusion: Older women with cervicogenic headache have localized pain sensitivity to cold stimuli, suggesting peripheral mechanisms underlie the hyperalgesia.